Analisis Pengaruh electronic Word of Mouth di Media Sosial Youtube Terhadap Minat Beli Produk Kosmetik Sariayu - Husna, Rahmatul; Dirgantara, I Made Bayu (Faculty of Economics and Business Diponegoro University, 2018)
Nowadays, in order to obtain information about a product is not only limited to the information that given from the manufacturer. But the information can also be obtained through other personal consumer, this is called with Word of Mouth communication. As the development of current technologies, Word of Mouth communication evolved into electronic Word of Mouth can be done with a wider range. Electronic Word of Mouth Communication can positive or negative statements that form of consumer opinion, potential consumers, as well as a former consumer about a product that can be accessed by anyone in the virtual world as social media that can affect the consumer interest in consuming these products. This research aims to know the existence of the electronic Word of Mouth influence against the interests of consumers against purchasing a product, especially cosmetic products Sariayu. This research uses nonprobability sampling technique by distributing questionnaires to 258 female respondents aged 17 to 29 years who use social media and find out information about Sariayu cosmetic products. The collected data is then analyzed by several tests such as validity test, reliability test, normality test, heteroskedasity test, multicollinearity test, multiple regression analysis, t test, F test and determination coefficient test (R2) using IBM SPSS software application 22 for Windows. Based on the results show that electronic Word of Mouth has positive and significant effect to purchase intention.